General Equilibrium Perception on Twin Deficits Hypothesis: An Empirical Evidence for the U.S. - Tuck , Cheong Tang; Lau, Evan (Monash University Business and Economics, 2009)
From the general equilibrium perceptive, this study proposes the inclusion of private savings and investments in examining twin deficits hypothesis. Using U.S. data, the empirical results support twin deficits hypothesis but the budget deficit’s elasticity is decreasing from unity to 0.43.